Pain experience and behavior management: efficacy of photobiomodulation as an adjunct to local anesthesia in MIH patients—a randomized split-mouth clinical study - Olszewska, Aneta; Roszak, Magdalena; Szymczak, Aleksandra; Paszyńska, Elżbieta; Czajka-Jakubowska, Agata (Frontiers in Neurology, 2025)
BackgroundPain management in children with Molar-Incisor Hypomineralization (MIH) poses challenges for pediatric dentists. MIH affects the enamel of the first permanent molars and incisors, increasing the risk of cavities, hypersensitivity, and making anesthesia and dental treatments more difficult. Children with MIH often experience dental fear, necessitating effective pain management techniques. Photobiomodulation (PBM) has potential analgesic benefits in dentistry but requires further evaluation for its effectiveness in MIH cases.AimThis study aimed to assess the impact of photobiomodulation on pain control in maxillary permanent molars affected by MIH.MethodsIn our randomized split-mouth clinical study, 45 participants (25 males, 20 females) aged 7 to 15 years, with both maxillary molars affected by MIH, were assigned to either the intervention group (PBM plus standard anesthesia, n = 45 teeth) or the control group (standard anesthesia alone, n = 45 teeth). PBM parameters included a power of 100 mW, a wavelength of 635 nm, energy of 6 J, fluence of 12 J/cm2, and a duration of 60 s. Pain perception, anesthesia commencement, and its extension time were measured and analyzed using SPSS version 23.0 (p < 0.05).ResultsThe PBM group reported significantly lower subjective pain (mean VAS 2 [1–5]) compared to the control group (6 [2–8]), p < 0.001. FLACC scale scores were also lower in the intervention group (3 [1–5]) compared to the control group (7 [5–8]), p < 0.001. The PBM group showed a lower heart rate (84.6 bpm ± 6.1) compared to the control (113.2 bpm ± 6.1), p < 0.001. Additionally, the anesthesia developed faster in the PBM group (mean: 3.6 ± 0.9 min) compared to the control (6.1 ± 0.8 min, p < 0.001), and the anesthetic effect persisted longer (70.2 ± 3.9 min vs. 50.7 ± 8.9 min, p < 0.001).ConclusionPhotobiomodulation improves pain management and the effectiveness of local anesthesia in maxillary molars affected by MIH by diminishing pain experience and enhancing anesthesia effects, providing a promising approach for pain control in children.